Cognitive function in euthymic bipolar disorder (BP I) patients with a history of psychotic symptoms vs. schizophrenia. Issue 1 (30th November 2015) - Nenadic, Igor; Langbein, Kerstin; Dietzek, Maren; Forberg, Anne; Smesny, Stefan; Sauer, Heinrich
Abstract: Patients with bipolar disorder show cognitive deficits including executive function, which appear to be related to social functioning and outcome. However, subgroups within the spectrum as well as psychopathological features, current mood state/euthymia and disease stage might be confounding factors. We analysed data tests from the Wechsler Intelligence Scale (WIE), verbal fluency (COWA) and trail making tests (TMT-A and TMT-B) obtained in a selected subgroup of currently bipolar I disorder patients, who were currently euthymic and had a history of psychotic symptoms, and compared them to patients with schizophrenia (in remission) and healthy controls, all matched for age, gender, and handedness. Schizophrenia patients showed more severe cognitive impairment, including digit symbol and arithmetic tests, as well as TMT-B (compared to healthy controls), but bipolar patients had stronger impairment on the letter number sequencing test, an indicator of working memory and processing speed. There were no group effects on most verbal fluency tasks (except impairment of schizophrenia patients on one subscale of category fluency). Within the limitations of the study design, our results suggest that even in subgroups of presumably more severely impaired bipolar patients, some cognitive dimensions might achieve remission, possibly related to considerable state effects at testing. Highlights: Euthymic bipolar I disorder patients with previous psychosis differ from schizophrenia patients on measures of working memory and processing speed. Schizophrenia patients vs. healthy controls had stronger impairment on digit symbol and arithmetic tests, and TMT-B Euthymic bipolar I disorder patients had stronger impairment on letter number sequencing